Comparative efficacy of diclofenac sodium gel and urea cream in preventing capecitabine-induced hand-foot syndrome: a randomized interventional study - Tandel, Pinakin T.; Krishnan, Chandralekha; Anandanarayanan, Anand Praveen Kumar; Kaur, Navjot; Nagalingam, Sathiyamoorthy Pattanam; Ravel, Naveen (International Journal of Research in Medical Sciences, 2025)
Background: The oral prodrug of 5-fluorouracil, capecitabine, is frequently used to treat breast and colorectal malignancies. The effectiveness of therapy is compromised by hand-foot syndrome (HFS), a typical dose-limiting hazard that frequently requires dose adjustments. Topical agents such as diclofenac sodium gel and urea cream have shown promise as prophylactic options for managing HFS. To compare the efficacy of diclofenac sodium gel and urea cream in preventing capecitabine-induced HFS. Methods: This randomized, open-label, double-arm interventional study included 100 adult patients with breast or gastrointestinal malignancies receiving capecitabine chemotherapy. Arm A (diclofenac sodium gel) and Arm B (urea cream) were the two groups into which participants were randomly assigned. According to the Common Terminology Criteria for Adverse Events (CTCAE v5.0), the main goal was to prevent grade 2 or above HFS during a 12-week period. HFS severity, modifications in capecitabine dosage and therapy discontinuations were secondary outcomes. Both descriptive and inferential techniques were used in the statistical analysis. Results: HFS developed in 48% of participants, with no significant difference between the diclofenac arm (26 participants) and the urea arm (22 participants) (p=0.42). Grade 1 HFS was most prevalent (41%), while grades 2 and 3 were infrequent (6%). Treatment interruptions due to HFS occurred in 6% of participants and capecitabine dose modifications were required in 5%, with no significant differences between the two arms. Both interventions demonstrated comparable efficacy in HFS prevention. Conclusions: Diclofenac sodium gel and urea cream are equally effective in preventing capecitabine-induced HFS, reducing its severity and maintaining treatment adherence.